Social geometry and the success of moral ideas: The case of capital punishment. Issue 3 (September 2015) - Phillips, Scott; Lapuck, Jacqueline
Abstract Black (1979, 2000a, b, 2002a, b) argues that the success of an idea depends on its social geometry. We extend Black's theory of ideas to include moral ideas – statements about the nature of right and wrong. To do so, we focus on former Supreme Court Justice Thurgood Marshall's hypothesis regarding death penalty opinions: If Americans were fully informed about the problems surrounding capital punishment they would become opposed to the sanction. Marshall's prediction seems to be supported by college classroom experiments in which students' support for the death penalty plummets after taking a course on the topic. But existing experiments have a curious methodological feature – the professors were "forthright" about their personal opposition to capital punishment. By injecting a moral idea into the experiment – the death penalty is wrong – the professors created a conundrum: Did students turn against the death penalty because information about the problematic nature of capital punishment was compelling, or because they gravitated toward a moral idea espoused by a close superior? The findings from our neutral college classroom experiment support the latter interpretation.